Tadashi Kawamata : Field Work - Orchard, Karin; Sprengel Museum, Hannover (Ostfildern-Ruit : Cantz Verlag Ostfildern-Ruit, 1997)
Parallel to his large-scale city fringe projects, Tadashi Kawamata has been continuously developing his Field Works since 1984. Kawamata's Field Work represent the artist's very personal way of coming to terms with the phenomenon of urban civilization. This catalogue documents the Field Work meanwhile realized by Kawamata in many of the world's big cities, including Tokyo, New York and Hannover. With the exhibition in Hannover, Kawamata's concept takes on a new dimension, for this is the first time that his makeshift cardboard shacks have made their way into a museum.
Tadashi Kawamata : Field work in Hannover, Sprengel Museum, Hannover, 10. Dezember 1997 - 1. März 1998
biog. p. 60-61
Duits
Engels
boek
Keywords: Kawamata, Tadashi